2020
DOI: 10.1111/nbu.12439
|View full text |Cite
|
Sign up to set email alerts
|

The challenges of defining a healthy and ‘sustainable’ diet

Abstract: Considerable debate exists about changes required to current diets

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 34 publications
0
35
0
1
Order By: Relevance
“…Low vitamin D status is not a problem peculiar to the UK, concentrations of 25(OH)D below 30 nmol/l are relatively common in Europe and there is a several‐fold higher risk of low vitamin D status among some ethnic minority groups. The first option on the WHO/FAO list is increasing the diversity of foods consumed but this has its challenges because there are very few food sources naturally rich in vitamin D. These are mainly of animal origin, which is highly relevant in the context of the recent calls for a radical transformation of the global food system, with emphasis on increased consumption of plant‐based foods and reductions in animal‐derived foods for many, as part of a more sustainable flexitarian‐type diet (see Buttriss 2020; Steenson & Buttriss 2020).…”
Section: Options For Increasing Vitamin D Intakementioning
confidence: 99%
“…Low vitamin D status is not a problem peculiar to the UK, concentrations of 25(OH)D below 30 nmol/l are relatively common in Europe and there is a several‐fold higher risk of low vitamin D status among some ethnic minority groups. The first option on the WHO/FAO list is increasing the diversity of foods consumed but this has its challenges because there are very few food sources naturally rich in vitamin D. These are mainly of animal origin, which is highly relevant in the context of the recent calls for a radical transformation of the global food system, with emphasis on increased consumption of plant‐based foods and reductions in animal‐derived foods for many, as part of a more sustainable flexitarian‐type diet (see Buttriss 2020; Steenson & Buttriss 2020).…”
Section: Options For Increasing Vitamin D Intakementioning
confidence: 99%
“…In this Special Issue of Nutrition Bulletin, we consider the public health rationales for sugar and saturated fat reduction and the benefits of increased fibre intake. Also considered is the justification and opportunities for diversifying sources of protein, in the context of the environmental impact of current global food systems and the challenges associated with feeding a more prosperous and expanding global population now and in the decades to come (Steenson & Buttriss 2020). These papers are provided by Sara Stanner and Ayela Spiro (public health rationale for sugars reformulation and the use of sweeteners); Professor Ingeborg Brouwer (public health rationale for reduction of saturated fatwhy is it important and what methods can we use to reduce saturated fat); Marta Lonnie and Professor Alex Johnstone (public health perspective on plant protein as part of a sustainable and healthy diet); and Professor Catherine Stanton and colleagues (benefits of dietary fibre with a focus on gut microbiota) (Koc ß et al 2020).…”
Section: Looking To the Futurementioning
confidence: 99%
“…1), the bridging of which would be expected to convey nutritional and health benefits (Cobiac et al 2016), as well as having a lower environmental impact (Carbon Trust 2016). See Steenson and Buttriss (2020) for a detailed discussion.…”
mentioning
confidence: 99%
“…2016; WWF 2017; Reynolds et al . 2019; Steenson & Buttriss 2020). For instance, the EAT‐Lancet authors suggested 50 g of beans, lentils and peas and 25 g of soy beans a day, while other models calculated the percentage increase in intake: 86% increase of beans, pulses and other legumes intake (from the current 14 g to the optimal intake of 26 g/day) (Scarborough et al .…”
Section: Introductionmentioning
confidence: 99%
“…2019). These discrepancies are, however, not surprising and stem from the heterogeneous methodological approaches used (Steenson & Buttriss 2020).…”
Section: Introductionmentioning
confidence: 99%